PEMANFAATAN WORTEL DALAM SEDIAAN MASKER UNTUK MENGATASI KULIT WAJAH BERMASALAH - Lahtie, Indana Yaumil; Usodoningtyas, Sri (Universitas Negeri Surabaya, 2021)
Facial skin needs special attention because facial skin is one of the body's organs that is most sensitive to touch and stimulation. The high level of air pollution and free radicals now makes skin prone to problems such as dry and acne prone skin. Carrots are a root crop that is rich in benefits for the skin. Carrots can brighten the skin, moisturize and help regenerate damaged skin tissue. The aim of the research journal is to analyze carrots as a raw material for masking to deal with problematic facial skin. Carrots contain beta-carotene which is useful for protecting the skin from UV rays. Carrot bulbs are also rich in vitamin A and antioxidants which are very good for making the skin brighter. The results of this study indicate that carrots in the preparation of masks can overcome problems on the facial skin, especially on facial skin with acne.Keywords: Masks, carrots, skin face